Experimental Studies at Company X: Provision of Media Posters and K3 Inspections on Knowledge of Worker Safety in the Warping Section - Rafika Rafika; Daru Lestantyo; Suroto Suroto (Universitas Aisyah Pringsewu, 2021)
The purpose of this study was to analyze the effect of giving poster media and K3 inspection on the safety knowledge of workers in the warping section at PT X. This study used a quasi-experimental type of research. This research was conducted at a convection industry company, namely PT X which is prone to work accidents from the results of a survey conducted by researchers. There are 62 employees in the warping division, namely 18 women and 44 men. Respondents in this study had a minimum age of 21 years and a maximum of 51 years with an average age of 33,32258 years. The majority of respondents have a high school education, which is 52 people (83.9%). Then there are 8 people with junior high school education (12.9%), and 2 people with S1 (3.2%), with a total of 62 people (100%). The average respondent worked for 8,2903 years, the minimum respondent worked 1 year and a maximum of 19 years. This means that 62 respondents have standard work experience of 8 - 9 years. Results of this study indicate that the provision of a Media Poster has an effect on Occupational Safety Knowledge. There is a positive influence between the Provision of Media Posters on Occupational Safety Knowledge. K3 Inspection of Occupational Safety Knowledge. K3 inspection has a positive effect on Occupational Safety Knowledge. Meanwhile, education, age and years of service as confounding variables have no effect on employee safety knowledge.Penelitianini bertujuan untuk mengetahuipengaruh pemberian media poster dan inspeksi K3 terhadap pengetahuan keselamatan kerja pada pekerja di bagian warping di PT X. Jenis dari penelitian ini adalah kuasi eksperimental. Penelitian ini dilakukan pada perusahaan industry konveksi yaitu PT X yang mana rentan terjadi kecelakaan kerja dari hasil survey yang dilakukan peneliti. Karyawan bagian warping adalah 62 orang yaitu 18 perempuan dan 44 laki-laki. Responden pada penelitian ini memiliki umur minimal 21 tahun dan maksimal 51 tahun dengan rata-rata berumur 33,32258 tahun. Responden mayoritas berpendidikan SMA yaitu berjumlah 52 orang (83,9%). Kemudian mereka yang berpendidikan SMP ada 8 orang (12.9%), dan S1 ada 2 orang (3.2%), dengan total 62 orang (100%). Rata-rata responden bekerja selama 8,2903 tahun, minimal responden bekerja 1 tahun dan maksimal 19 tahun. Hal ini berarti dari 62 responden mereka memiliki pengalaman kerja standar 8 - 9 tahun. Hasil penelitian ini menunjukkan bahwa pemberian Media Poster berpengaruh terhadap Pengetahuan Keselamatan Kerja. Terdapat pengaruh positif antara Pemberian Media Poster terhadap Pengetahuan Keselamatan Kerja. Inspeksi K3 terhadap Pengetahuan Keselamatan Kerja, Inspeksi K3 berpengaruh positif terhadap Pengetahuan Keselamatan Kerja. Sedangkan Pendidikan, usia dan masa kerja sebagai variable perancu tidak memiliki pengaruh terhadap Pengetahuan Keselamatan Kerja karyawan.